2016
DOI: 10.1002/pc.24179
|View full text |Cite
|
Sign up to set email alerts
|

Study of the electroconductive properties of conductive polymers‐graphene/graphene oxide nanocomposites synthesized via in situ emulsion polymerization

Abstract: The present study introduces a modified approach to synthesize polyaniline (PANI) and polypyrrole (PPy) doped with graphene oxide (GO) or graphene (GN) through an in situ emulsion polymerization (EP) technique. Dodecyl benzene sulfonic acid (DBSA) was used as a surfactant and doping agent as well during the polymerization reaction. The morphology and microstructure of the synthesized polymers and their nanocomposites were studied by scanning electron microscopy, transmission electron microscopy, Fourier transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Besides, the XPS survey spectra (Figure 1j,k) with the N element peak in the full spectra was also can be used to certify the existence of PPy coating due to the non‐N element for the original GFs. And the fitted N 1S peaks at 400, 401, and 402 eV can be attributed to NH, NH + , NH + , further demonstrating the successful synthesis of PPy coating 18 …”
Section: Resultsmentioning
confidence: 72%
“…Besides, the XPS survey spectra (Figure 1j,k) with the N element peak in the full spectra was also can be used to certify the existence of PPy coating due to the non‐N element for the original GFs. And the fitted N 1S peaks at 400, 401, and 402 eV can be attributed to NH, NH + , NH + , further demonstrating the successful synthesis of PPy coating 18 …”
Section: Resultsmentioning
confidence: 72%
“…The X-ray diffraction pattern of NGO and NGPPC was investigated (Figure 2b). The peaks at 2θ = 11 and 26 • are referred to the inter-planar spacing increase of oxidation treatment and residual unoxidized graphite, respectively [31]. Presence of a slightly broad peak at 2θ = 11.5 • is related to characteristic peak of pyrole in NGPPC structure which proves the incorporation of pyrrole in NGO structure.…”
Section: Ngppc Characterizationmentioning
confidence: 93%
“…Peak at 1703 cm −1 is referred to carboxylic C=O functional group of NGO. The peaks at 2θ = 11 and 26 • are referred to the inter-planar spacing increase of oxidation treatment and residual unoxidized graphite, respectively [31]. FTIR spectrum of NGPPC was studied.…”
Section: Ngppc Characterizationmentioning
confidence: 99%
“…Kim et al. [ 64,65 ] reported a similar in situ emulsion polymerization to prepare PANI and PPy nanocomposites containing 5 wt% of GO with outstanding electrical properties. In this study, they simultaneously applied dodecyl benzene sulfonic acid (DBSA) as an emulsifier and protonating agent to initiate the formation of PANI and PPy during the polymerization reaction.…”
Section: In Situ Emulsion Polymerization To Prepare Polymer Nanocompo...mentioning
confidence: 99%
“…The PPy nanowires will deposit onto the GO surface because of the 𝜋-𝜋 interaction and electrostatic interaction between PPy and the unoxided domain of GO sheets, resulting in to the formation of layered PPy/GO composite with excellent electrical conductivity. Kim et al [64,65] reported a similar in situ emulsion polymerization to prepare PANI and PPy nanocomposites containing 5 wt% of GO with outstanding electrical properties. In this study, they simultaneously applied dodecyl benzene sulfonic acid (DBSA) as an emulsifier and protonating agent to initiate the formation of PANI and PPy during the polymerization reaction.…”
Section: Polymer Nanocomposites Containing Carbon-based Nanofillersmentioning
confidence: 99%